Easter microplate dynamics - Neves, MC (2018)
[1] We use two-dimensional elastic finite element analysis, supplemented by strength estimates, to investigate the driving mechanism of the Easter microplate. Modeled stresses are compared with the stress indicators compiled from earthquake focal mechanisms and structural observations. The objective is to constrain the tectonic forces that govern the Easter microplate rotation and to test the microplate driving hypothesis proposed by Schouten et al. [1993]. We infer that the mantle basal drag cannot drive the microplate rotation but opposes it, and that the asthenospheric viscosity is no more than about 1 x 10(18) Pa s. At most, the basal drag comprises 20% of the force resisting microplate rotation. The outward pull of the main plates can drive the rotation by shear drag applied along the northern and southern boundaries of the microplate. However, we propose an additional driving force which arises from the strong variation of the ridge resistance force along the east and west rifts, so that the main driving torques come from the pull of the major plates acting across the narrowing and slowing rifts. This requires the strength to increase substantially toward the rift tips due to thickening of the brittle lithosphere as the spreading rate slows.